Bone: From planar imaging to SPECT & PET/CT - Mihailović Jasna (Archive of Oncology, 2012)
Since its introduction into clinical medicine 50 years ago, the radionuclide bone scan has played a key role in diagnosing a variety of osseous disorders; particularly metastatic disease. Using small diagnostic doses of Strontium-85 in the 1960’s, it was rapidly established that the study was much more sensitive than skeletal radiographs. The introduction of Technetium-99m phosphate agents in the early 1970’s, offered greatly improved resolution. Whole body imaging became the standard procedure. Interestingly, the positron-emitter, Fluorine 18-sodium fluoride was used by some investigators with the rectilinear scanner. Very recently, this radiotracer has been re-introduced and is witnessing considerable growth using modern PET/CT instrumentation. The cortical bone tracers, 99mTc-MDP and 18F-Fluoride assess osteoblastic response to the invading lesion. In the study of metastatic disease, it is superb for sclerotic blastic lesions. Although it detects most lytic lesions, many can be missed. This is due to a lack of osteoblastic response. The tumor may be slow growing, such as myeloma or conversely very rapidly growing and destructive, such as lung or kidney metastases. In these lesions, 18F-FDG is superior because it is concentrating in the tumor cells and does not depend on osteoblastic response to the tumor. In their early cause, many lytic lesions may be confined to the medullary portion of bone and not yet involve the cortex. Comparative studies of PET and CT have clearly shown the superior sensitivity of FDG in detecting metastatic bone lesions.